Chondrocyte secretome: a source of novel insights and exploratory biomarkers of osteoarthritis. Issue 8 (August 2017) - Sanchez, C.; Bay-Jensen, A.-C.; Pap, T.; Dvir-Ginzberg, M.; Quasnichka, H.; Barrett-Jolley, R.; Mobasheri, A.; Henrotin, Y.
Summary: The extracellular matrix (ECM) of articular cartilage is comprised of complex networks of proteins and glycoproteins, all of which are expressed by its resident cell, the chondrocyte. Cartilage is a unique tissue given its complexity and ability to resist repeated load and deformation. The mechanisms by which articular cartilage maintains its integrity throughout our lifetime is not fully understood, however there are numerous regulatory pathways known to govern ECM turnover in response to mechanical stimuli. To further our understanding of this field, we envision that proteomic analysis of the secretome will provide information on how the chondrocyte remodels the surrounding ECM in response to load, in addition to providing information on the metabolic state of the cell. In this review, we attempt to summarize the recent mass spectrometry-based proteomic discoveries in healthy and diseased cartilage and chondrocytes, to facilitate the discovery of novel biomarkers linked to degenerative pathologies, such as osteoarthritis (OA).